Implementasi Kaidah Al-Yaqinu La Yuzalu Bi Al-Syakki Dalam Ibadah - Fitri Amanda Hsb; Tasya Afrianti; M. Yusuf Alamsyah; Dicky Alamsyah Pardede; Rayhan Riend al-Afiq; Rahmad Hidayat (Tabayyun : Journal Of Islamic Studies, 2025)
The rule (qaidah) of Al-Yaqinu La Yuzalu bi Al-Syakki is present as a fundamental principle that provides guidance in dealing with these doubts. This rule was first formulated by classical scholars and continues to develop into one of the important pillars in decision-making of Islamic law. This study examines the implementation of the fiqh rules